The White Tiger - Adiga, Aravind (London Atlantic Books, 2008)
No saris. No scents. No spices. No music. No lyricism. No illusions. This is India now. Balram Halwai is a complicated man. Servant. Philosopher. Entrepreneur. Murderer. Over the course of seven nights, by the scattered light of a preposterous chandelier, Balram tells us the terrible and transfixing story of how he came to be a success in life-having nothing but his own wits to help him along. Born in a village in the dark heart of India, Balram gets a break when he is hired as a driver for a wealthy man, two Pomeranians (Puddles and Cuddles), and the rich man's (very unlucky) son. Through Balram's eyes, we see India as we've never seen it before: the cockroaches and the call centers, the prostitutes and the worshippers, the water buffalo and, trapped in so many kinds of cages that escape is (almost) impossible, the white tiger. And with a charisma as undeniable as it is unexpected, he teaches us that religion doesn't create morality and money doesn't solve every problem-but decency can still be found in a corrupt world, and you can get what you want out of life if you eavesdrop on the right conversations.
Man Booker Prize for Fiction, 2008.
Keywords: Poor -- Poor -- India -- Bangalore -- Fiction. -- Chauffeurs -- India -- Bangalore -- Fiction